2015
DOI: 10.4103/0970-2113.168129
|View full text |Cite
|
Sign up to set email alerts
|

Burden of obstructive lung disease study in Tehran: Prevalence and risk factors of chronic obstructive pulmonary disease

Abstract: Background:Chronic obstructive pulmonary disease (COPD) was ranked the sixth-most common cause of death worldwide in 1990, but now it is the third-most common cause. The goal of the present study was to assess the prevalence and determine the causes and risk factors of COPD in Tehran.Materials and Methods:This study followed a stratified cluster sampling strategy with proportional allocation within strata. The target population was all non-institutionalized inhabitants, aged 18 to 40 in one group and over 40 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…[34] In another study, male sex, increasing age, and smoking history were strong risk factors for COPD, and these associations remained significant after adjustment for other variables. [35] This situation is similar to our previous study in Tehran[13] and posed the hypothesis that considering lower prevalence of tobacco smoking, other risk factors such as air pollution and fossil fuel pollution levels could have a greater effect in women compared with men.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…[34] In another study, male sex, increasing age, and smoking history were strong risk factors for COPD, and these associations remained significant after adjustment for other variables. [35] This situation is similar to our previous study in Tehran[13] and posed the hypothesis that considering lower prevalence of tobacco smoking, other risk factors such as air pollution and fossil fuel pollution levels could have a greater effect in women compared with men.…”
Section: Discussionsupporting
confidence: 85%
“…[101112] In our previous study, we found that the prevalence of airflow limitation was higher in individuals who had ever smoked, but among patients with COPD according to the spirometry tests, 12.6% were smokers and 18.3% ex-smokers. [13] In other words, nonfully reversible airflow obstruction also occurs in never smokers. Iran is a developing country where the smoking rate (11.9%) is lower than the observed in many developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking and exposure to environmental tobacco smoke have been proved to be the strongest risk factors for airflow obstruction,[ 12 ] but many areas of the world with high mortality rates from “COPD” still have low consumption of tobacco, implying that tobacco smoking alone does not explain the distribution of COPD. [ 13 14 15 ] In our previous studies, we found that the prevalence of airflow limitation was higher in individuals who had ever smoked or been passive-smoker,[ 16 17 ] but was prevalent in never-smokers as well. Iran is a developing country where the smoking rate is lower than in many developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 5% of the world's population is affected by COPD, such that it was the third leading cause of death in 2012. The prevalence of this health problem is expected to rise to the extent that by 2020 it will be one of the top three causes of mortality in the world (2)(3)(4). Based on official statistics, an average of 14% of Iranians have COPD, varying from 0.4% to 1% across communities with different weather conditions (4).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of this health problem is expected to rise to the extent that by 2020 it will be one of the top three causes of mortality in the world (2)(3)(4). Based on official statistics, an average of 14% of Iranians have COPD, varying from 0.4% to 1% across communities with different weather conditions (4). Due to its debilitating nature, COPD imposes direct and indirect costs to the healthcare system, society, and the patient (5).…”
Section: Introductionmentioning
confidence: 99%